Tailoring Metal Phthalocyanine/Graphene Interfaces for Highly Sensitive Gas Sensors - Daniele Perilli; Alberto Maria Rizzi; Cristiana Di Valentin (Nanomaterials)
Developing novel gas-sensing materials is critical for overcoming the limitations of current metal oxide semiconductor technologies, which, despite their widely commercial use, require high operating temperatures to achieve optimal performance. In this context, integrating graphene with molecular organic layers provides a promising platform for next-generation gas-sensing materials. In this work, we systematically explore the gas-sensing properties of metal phthalocyanine/graphene (MPc/Gr) interfaces using density functional theory calculations. Specifically, we examine the role of different MPcs (FePc, CoPc, NiPc, and CuPc) and Gr doping levels (p-doped, neutral, and n-doped) in the detection of NH3 and NO2 molecules, used as representative electron-donor and -acceptor testing gases, respectively. Our results reveal that a p-doped Gr is necessary for NH3 detection, while the choice of metal cation plays a crucial role in determining sensitivity, following the trend FePc/Gr > CoPc/Gr > NiPc/Gr, with CuPc/Gr exhibiting no response. Remarkably, FePc/Gr demonstrates sensitivity down to the limit of a single NH3 molecule per FePc. Conversely, NO2 detection is possible under both neutral and n-doped Gr, with the strongest response observed for n-doped FePc/Gr and CoPc/Gr. Crucially, we identify the dz2 orbital of the MPc as a key factor in mediating charge transfer between the gas molecule and Gr, governing the electronic interactions that drive the sensing response. These insights provide valuable guidelines for the rational design of high-sensitivity graphene-based gas sensors.